Prevalence and risk factors of fish-borne zoonotic trematode infections in a rural community: A cross-sectional study in the Red River Delta of Vietnam - Canh, Hoang Dinh; Loi, Cao Ba; Tuan, Nguyen Van; Thoai, Nguyen Van; Tan, Nguyen Duc; Quynh, Nguyen Thi Nhu; Du, Vu Van; Anh, Do Ngoc (Journal of public health research, 2025)
Background: To our knowledge, there is a lack of reports on the prevalence and risk factors of fish-borne zoonotic trematodiasis (FZTi) in humans in many regions of Vietnam. Design and methods: A cross-sectional study was performed in three communes located in the Red River Delta, northern Vietnam, where residents are reported to have a habit of eating raw freshwater fish, between June 2020 and December 2021. A total of 591 individuals were interviewed using structured questionnaires, and their stool samples were collected for the analysis of fishborne zoonotic trematode (FZT) egg presence using direct microscopic observation and the formalin-ether concentration method. Univariate and multivariable logistic regression analyses were employed to explore potential risk factors. Results: The prevalence of fish-borne zoonotic trematodiasis (FZTi) was 14.89% among the 591 participants, ranging from 1.52% to 39%. The average age of the participants was 48.31 ± 16.77 years (range: 7–86 years old), and the highest prevalence of FZT infection (17.36%) was observed in individuals aged 19–39 years, followed by those aged 40–59 (16.67%). The prevalence of FZT infectionwas higher in men (17.75%) than in women (11.07%). Factors independently associated with FZTi, obtained by multivariate analysis, included a history of eating raw freshwater fish and the study commune. Conclusions: The present study has revealed a wide-ranging prevalence of FZTi among humans in Vietnam’s Red River Delta. Sustained surveillance efforts for FZTi, as well as the implementation of long-term, practical control policies, and strategies for eliminating FZT in Vietnam, are still necessary.